The Influence of Transformational Leadership, Emotional Intelligence, Organizational Climate, and Teamwork, Towards Organizational Citizenship Behavior of Civil Servants - Hamid, Fadlun A; Widodo, Suparno Eko; Buchdadi, Agung Dharmawan (International Journal for Applied Information Management, 2022)
The purpose of this study was to ascertain the direct positive effect of transformational leadership, emotional intelligence, organizational climate, and teamwork on the organizational citizenship behavior of civil servants at the Central Sulawesi Province Education and Culture Office. The novelty of this research is that no prior study has examined the effect of transformational leadership, emotional intelligence, organizational climate, and teamwork on the organizational citizenship behavior of Civil Servants at the Education and Culture Office of Central Sulawesi Province, both methodologically and practically. This research employs a survey method and falls under the category of quantitative research. The population of this study was 433 individuals, and the sample size was 100 individuals drawn using a random sampling technique. Interviews, questionnaires, and documentation studies were used to collect data. The findings of this study are as follows: (1) transformational leadership (X1) and organizational climate (X3) have a direct positive effect on organizational citizenship behavior (Y); (2) emotional intelligence (X2) and organizational climate (X3) have a direct positive effect on teamwork (X4); (3) emotional intelligence and teamwork have no direct positive effect on organizational citizenship behavior; and (2) transformational leadership does not have a direct positive effect on organizational citizenship behavior.